An Experimental Investigation Of A Weather Buoy-Wireless Data Acquisition Based On Microcontroller - Wibowo Harso Nugroho; Kusnindar Kusnindar; Mesawati Mesawati; Syamsul Arifin (Muhammadiyah University, Sidoarjo, 2017)
This paper presents an experimental work to monitor data acquisition of weather buoy by applying measurement sensors and wireless communication technology. The sensors were used to measure air pressure , air temperature, humidity, wind velocity, wind direction and the global position. Specifically, the communication of data acquisition system used in the weather buoys was developed using wireless modems and data communications software. Commands were issued from a computer to instruct the data acquisition system to acquire data from sensors. The RMS of each component is recorded and entered into the measurement range of 0.28-0.69 %. This range changes slightly when they were incorporated into the data acquisition system with the error of RMS 1.761% . However this was still in a good performance since the RMS error was less than 2%.